Archives in drag: Performing nachaniya towards a queer theory of indenture. Issue 1 (8th July 2022) - Persard, Suzanne C.
Abstract : 'Archives in drag: Performing nachaniya towards a queer theory of indenture' takes as its object the figure of the Indo-Jamaican nachaniya dancer as a paradigm for re-thinking queer theories of indenture. Nachaniya is a highly stylized Indo-Jamaican folk dance featuring a heterosexual male dancing in drag. The performance, which can be traced to the nineteenth century, is still common within present-day Indo-Jamaican communities and the diaspora. Nachaniya therefore presents both parts of a queer historical and living archive. By using an archival photograph from the 1960s of a nachaniya dancer as a point of entry, I consider the ways in which this genre of Indo-Jamaican folk performance demonstrates gender non-normativity as deeply embedded within the indentured archive. Since nachaniya is also read as not necessarily queer but 'cultural', I am interested in the tensions between a refusal to categorize the performance as a kind of drag while simultaneously elevating its 'cultural' status and the slippage between 'queer' and 'culture'. I consider the figure of the nachaniya dancer as what Anjali Arondekar has termed a site of 'ordinary surplus' rather than a site of queer exception. Through a reading of this queer archival photograph, I consider destabilizing narratives of loss or absence that saturate approaches to the queer archive of indenture to suggest that nachaniya is a useful paradigm for theorizing the nexus at which Indo-Jamaican archives and queers of indenture have been theorized as 'nothing to see'.